Application of Sol-Gel Synthesized Cu-TiO₂/ZnO Photocatalyst for Textile Dye Wastewater Treatment - David Kevin (Research in Chemical Engineering, 2026)
The textile dyeing industry is the second largest water polluter in the world, with the industry generating 20% of the world's total wastewater effluent. Methylene blue is one of the most commonly used textile dyes, causing degradation of aquatic ecosystem quality. A new method that can help in the treatment process of liquid waste that has a relatively low cost, one of which is a photocatalyst using material  and using the sol gel method. This photocatalyst was tested by characterization using SEM, UV-Vis DRS, and UV-Vis Spectrometer. The results of SEM characteristics show that the particles are spherical with varying particle sizes. The UV-Vis DRS results show that the Eg values obtained are 3.186 eV for TiO₂/ZnO, 2.296 eV for Cu(5%)-TiO₂/ZnO, and 2.162 eV for Cu(8%)-TiO₂/ZnO. The concentration of methylene blue affects the effectiveness of degradation with the highest degradation at 5 ppm of 77.51%, at 10 ppm of 67.02% and 15 ppm of 54.30%. In conclusion, the sol-gel synthesized Cu-TiO₂/ZnO photocatalyst demonstrates promising effectiveness for textile dye wastewater treatment, with optimized Cu doping significantly enhancing visible-light absorption and degradation efficiency of methylene blue.